Hexylaminolevulinate‐mediated fluorescent urine cytology with a novel automated detection technology for screening and surveillance of bladder cancer. (16th April 2021) - Miyake, Makito; Nakai, Yasushi; Nishimura, Nobutaka; Ohnishi, Sayuri; Oda, Yuki; Fujii, Tomomi; Owari, Takuya; Hori, Shunta; Morizawa, Yosuke; Gotoh, Daisuke; Anai, Satoshi; Torimoto, Kazumasa; et al.
Abstract : Objectives: To evaluate the diagnostic performance of fluorescent voided urine cytology (FVUC) using a novel automated detection technology to screen for primary bladder cancer and for surveillance of recurrent bladder tumour. Patients and Methods: We created a rapid, objective, automated, and high‐throughput detection device for hexylaminolevulinate‐mediated FVUC, named the cellular fluorescence analysis unit‐II (CFAU‐II). Two different cohorts were used in this study: (i) screening test for primary bladder cancer (165 patients with bladder cancer and 52 controls), and (ii) surveillance test for detecting intravesical recurrent tumour (192 patients with treated non‐muscle‐invasive bladder cancer and 15 with post‐nephroureterectomy upper urinary tract cancer). Voided urine samples were subjected to urine analysis, conventional VUC (cVUC), and FVUC. Diagnostic performance was compared between cVUC, FVUC, and a combination of the two. Results: A total of 614 urine samples were successfully collected, processed, and analysed. Comparative analysis of the screening test cohort demonstrated that the overall sensitivity of FVUC (63%, P < 0.001) and combination testing (72%, P < 0.001) was significantly higher than that of cVUC (29%). FVUC was found to be superior in most of the subgroups, especially in low‐grade, Ta, and small tumours. Analysis of the surveillance test cohort showed that combination testing achieved a sensitivity of 82% and a negative predictive value of 98%, whereas those of cVUC were 39% and 96%, respectively. According to the pathological finding of recurrent tumours presenting false‐negative result in the FVUC, the majority of the overlooked recurrent diseases were Ta low‐grade tumours. Logistic regression analysis suggested an association between the risk of false‐positive results and high density of urine white blood cells and alkaluria. Conclusion: The present findings clearly demonstrate that FVUC using the newly developed automation technology has superior sensitivity to cVUC for both screening for primary bladder cancer and recurrent tumour detection. It is essential to confirm the clinical usefulness of this method via further large‐scale studies, in addition to ensuring its affordability and availability.